Bitter poison : a village mystery - Mayhew, Margaret, 1936- (Mayhew, Margaret, 1936- Village mystery., 2016)
The British town of Frog End is preparing for its annual Christmas pantomime. Local busybody Marjorie Cuthbertson is on the hunt for her leading lady - and who better that beautiful new resident,ex-model Joan Dryden. Mystery is about to engulf the village, however, when a cast member collapses and dies at the Christmas party at the Manor, having consumed a rogue mince pie. Was the death and accident - or a malicious murder masked asn an allergic reaction? The Colonel is about to be dragged into the role of reluctant village sleuth yet again.